Improving Students’ Speaking Ability by Using Escape Room Technique at the Eight Grade of SMP Yabes School Medan - Sinaga, Imelda Fitriyani; Anggraini, Risa (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research aimed to improve students’ speaking ability by using Escape Room technique at the eighth grade of SMP Yabes Medan. The researchers applied Classroom Action Research (CAR) which consisted of two cycles, and each cycle included planning, action, observation, and reflection. The subjects of this research were 28 students of class VIII. Two types of data were collected in this study, quantitative and qualitative. Quantitative data were obtained through speaking tests, while qualitative data were gathered through interviews, observations, and documentation. Researchers used speaking test to collect the quantitative data, meanwhile in qualitative data, researchers used interview, observation, and documentation. After conduction two cycles, the findings showed the mean score of students’ speaking test increased from 74,64% in the first cycle to 86,96%. In addition, classroom atmosphere became more engaging and enjoyable, which reduced students’ anxiety in speaking English and also provides a fun and interactive learning environment that encourages students to use English more actively in communication.